Postoperative nausea and vomiting - Smith, Howard S.; Smith, Eric J.; Smith, Benjamin R. (Annals of Palliative Medicine; Vol 1, No 2 (July 14, 2012): Annals of Palliative Medicine, 2012)
Postoperative nausea and vomiting (PONV) remains a significant clinical issue that can detract from patients’ quality of life in hospital/treatment facility, as well as in the days immediately postdischarge. In addition, PONV may increase perioperative costs, increase perioperative morbidity, increase postanesthesia care unit stay, prolong hospital stays, length of stay/delay discharge, delay the time that the patient can go back to work, and lead to readmissions. Despite the existence of multiple tools to stratify patients according to their risk of developing PONV and multiple PONV treatment guidelines, clinicians do not appear to systematically address the treatment and/or prophylaxis of PONV in a uniform fashion with both pharmacologic and nonpharmacologic strategies in attempts to minimize PONV occurrences.